Effectiveness of Problem-Based Learning Supported by PELIP Media on Elementary School Students Understanding of Probability - Pitriyani Pitriyani; Maulana Maulana; Ani Nur Aeni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Probability is one of the subjects that students must master by the end of Phase C in elementary school. To help students understand probability concepts more clearly, the Problem-Based Learning (PBL) approach and the PELIP medium were used. This study aims to examine how the use of the Problem-Based Learning (PBL) approach supported by the PELIP medium, the use of the PELIP medium itself, and the PBL approach influence elementary school students’ understanding of probability concepts. This study employs a quantitative method with an experimental design. This study was conducted at two elementary schools SDN Cimasuk and SDN Lembang located in Pamulihan Subdistrict, Sumedang Regency, involving three groups that received different treatments. Data were collected through tests standards for validity, reliability, difficulty level, and the ability to distinguish between answers. Data analysis was conducted by examining baseline conditions, comparing differences between groups, measuring improvement within each group, and calculating N-Gain values. The results of the study show that all types of interventions successfully improved students’ understanding of probability concepts. The PBL class that used the PELIP medium saw its average score increase from 37.53 to 76.50, with an N-Gain of 0.63. The class using the PELIP medium saw its average score rise from 45.50 to 74.94, with an N-Gain of 0.56. Meanwhile, the PBL class’s scores increased from 40.35 to 80.06 with an N-Gain of 0.68, making it the group with the highest score increase. PBL approach using PELIP media, the use of PELIP media alone, and the PBL approach without PELIP media were all equally effective in improving elementary school students’ conceptual understanding of probability